Predisposing Factors and Surgical Management of Obstructive Sleep Apnoea in Children (Bangladesh Medical Journal, 2019)
Obstructive sleep apnoea (OSA) is a condition characterized by episodic partial or complete obstruction of the upper airway during sleep. This cause apnoea or cessation of breathing. During sleep, muscles around the airway relax causing the throat and upper airway to narrow. This leads to snoring, but it can also lead to the airway being blocked. Trying to breathe against a blocked airway causes oxygen levels to fall and carbon dioxide to rise. This cross-sectional study was conducted in Department of ENT, Dhaka Shishu (Children) Hospital and Dhaka Medical College Hospital from April to September’2015. The purpose of the study was to prevent significant morbidity and enhancement of child growth. One hundred children of OSA were studied by detail history and clinical examination. All children whose parents consulted their ENT surgeon in Dhaka Shishu(Children) Hospital and DMCH for snoring or laboured breathing during sleep (nocturnal sweating particularly in the nuchal area, unusual sleeping positions, restless sleep, awakening and excessive movements, intercostals recession and dry mouth) were included in the study. More common predisposing conditions for OSA were obesity and Craniofacial anomalies which were 34% and 27% respectively. In present study most of the children (73%) were managed by Adenotonsillectomy and 27% children were manage by Adenoidectomy. Outcome data have demonstrated that surgical therapy can be successful in the treatment of OSA.Bangladesh Med J. 2017 May; 46 (2): 22-25